A new approach for processing X-ray data for detecting mini-halos in galaxy clusters - Jafar, Zareef; Mim, Armin Nahar; Roy, Sworna (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.